Effect of virgin coconut oil (VCO) on the physical stability of sweet potato leaf extract (Ipomoea batatas (L.) Lam) creams and antibacterial activity test against Staphylococcus aureus ATCC 25923 - Mauritz Pandapotan Marpaung; Dani Prasetyo (Universitas Ahmad Dahlan, 2021)
VCO (virgin coconut oil) has benefits for skin health such as softening the skin, maintaining skin health, and protecting the skin from radiation and free radicals. VCO as one of the raw materials for making cream preparations can affect its physical stability. This study aimed to analyze the effect of VCO on the physical stability of sweet potato leaf extract creams and antibacterial activity test against Staphylococcus aureus ATCC 25923. The creams were made with five formulas namely base, extract cream 2%, and VCO 1%, 3%, 5% added to the extract cream 2% respectively. Physical stability test included storage for six weeks at room temperature. Stability parameters were organoleptic observation, homogeneity, pH, spreadability, adhesivity, and cream type. Statistical analysis was carried out with the Anova and Kruskal Wallis tests. The organoleptic test results of the cream extract showed a distinctive odor, green color, with semisolid and homogeneous texture. Increasing the concentration of VCO will increase the spreadability of extract cream but did not affect pH and adhesion. The conclusion of this study was that extract cream 2% without the addition of VCO was the most stable cream formulation. Besides that, all the cream formulas did not show antibacterial activity against Staphylococcus aureus ATCC 25923.